Do equity prices reflect the ultra-low interest rate environment? - Søren Lejsgaard Autrup; Jonas Ladegaard Hensch (Danmarks Nationalbank, 2020)
Economic Memo is a new publication series from Danmarks Nationalbank. Please, update your News service settings if you want to receive a notification when the next Economic Memo is available. The first Economic Memo shows that the equity risk premium has doubled after the financial crisis. As a result, financing costs of corporations declined less than monetary policy rates. The memo looks into explanations behind the higher premium.
Keywords: 330; Risikoprämie; Wirtschaftslage; Geldpolitik; Dänemark